The advantage of playing less sets than the opponent in the previous two rounds of Grand Slam tennis tournaments - O`Donoghue, P. (Journal of Sports Sciences, 2006)
To win a Grand Slam tennis tournament, a player must win seven matches within 2 weeks. Because tennis is a score-dependent rather than time-dependent sport, some matches may be longer than others resulting in fatigue and performance decrements. The purpose of the current investigation was to compare the performance of the higher and lower ranked player within Grand Slam singles matches where they had played different numbers of sets in the previous 2 rounds of the tournament. The result in sets of each of the 243 completed ladies` and men`s singles match played in the 4 Grand Slam tournaments in 2002 from the 3rd round to the final were accessed from the tournaments` web sites. For each match, the difference in the number of sets the higher and lower ranked players played in the previous 2 rounds was also recorded. Tables 1 and 2 show (for ladies` and men`s singles respectively) the outcome of matches for a range of situations arising from the previous 2 rounds of the tournament. For ladies` singles, a Kruskal Wallis H test revealed a significant effect on the higher ranked player`s performance of playing more sets than the opponent over the previous two rounds (c24 = 12.5, P < 0.05). Indeed, the mean rank for the higher ranked player`s performance decreased as the difference between the player and her opponent for the number of sets played in the previous 2 rounds increased. For men`s singles, a Kruskal Wallis H test did not reveal any significant effect on the higher ranked player`s performance of playing more sets than the opponent over the previous two rounds (c26 = 3.6, P > 0.05). The current study provides evidence that requiring 3 sets to defeat an opponent in ladies` singles can increase the risk of losing subsequent matches. Future work is recommended to further explore relationships between performances in matches and preceding matches within tournaments using process indicators as well as outcome indicators.